Research and Application for Grey Relational Analysis in Multigranularity Based on Normality Grey Number - Jin Dai; Xin Liu; Feng Hu (The Scientific World Journal)
Grey theory is an essential uncertain knowledge acquisition method for small sample, poor information. The classic grey theory does not adequately take into account the distribution of data set and lacks the effective methods to analyze and mine big sample in multigranularity. In view of the universality of the normal distribution, the normality grey number is proposed. Then, the corresponding definition and calculation method of the relational degree between the normality grey numbers are constructed. On this basis, the grey relational analytical method in multigranularity is put forward to realize the automatic clustering in the specified granularity without any experience knowledge. Finally, experiments fully prove that it is an effective knowledge acquisition method for big data or multigranularity sample.